2015
DOI: 10.1590/1679-78251300
|View full text |Cite
|
Sign up to set email alerts
|

Primary and Reflected Compaction Waves in a Foam Rod Due to an Axial Impact by a Small Mass

Abstract: The propagation of compaction waves in a stationary foam block subjected to an impact by a small mass is studied in order to examine the mechanism of compaction within the primary and reflected stress waves. The analysis is focused on aluminium strain rate insensitive foam that exhibits strain hardening under quasistatic compression. A theoretical approach is applied using a uniaxial model of compaction in which the compacted strains, being functions of the velocity variation, are not predefined but are obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Refs. [147][148][149] ( ) P t In the theoretical framework of continuum mechanics, unified 1D shock models have been developed by Karagiozova et al [172,255,[260][261][262] and Zheng et al [106,169] mainly for the first two loading scenarios shown in Table 3 Examples of typical plasticity models for cellular materials are listed in Many studies have shown that the yield surfaces described by the plasticity models summarised in Table 5 are in reasonably good agreement with experimental results for multiaxial loading [14,60,62,272,274,275] (e.g. Fig.…”
Section: ]mentioning
confidence: 79%
“…Refs. [147][148][149] ( ) P t In the theoretical framework of continuum mechanics, unified 1D shock models have been developed by Karagiozova et al [172,255,[260][261][262] and Zheng et al [106,169] mainly for the first two loading scenarios shown in Table 3 Examples of typical plasticity models for cellular materials are listed in Many studies have shown that the yield surfaces described by the plasticity models summarised in Table 5 are in reasonably good agreement with experimental results for multiaxial loading [14,60,62,272,274,275] (e.g. Fig.…”
Section: ]mentioning
confidence: 79%
“…A new compaction resulting from the wave reflected from the stationary boundary can arise at t ¼ t 1 if the initial impact energy is not entirely absorbed within the primary wave (Karagiozova and Alves, 2015). At t ¼ t 1 , the compacted cellular block has thickness L 1 ¼ hðt 1 Þ, which depends on the initial impact velocity and striking mass.…”
Section: Impact Of a Stationary Cellular Block By A Rigid Massmentioning
confidence: 99%
“…The equations of motion for t > t 1 with respect to the new compacted zone with thickness h 2 and additional displacement u 2 are (Karagiozova and Alves, 2015) dV…”
Section: Impact Of a Stationary Cellular Block By A Rigid Massmentioning
confidence: 99%
“…The kinetic energy amplitude of each honeycomb was similar before 0.009 s, and the fluctuation period were similar. This was explained on shock waves in cellular materials by Karagiozova and Alves 44 ; the fluctuation might be caused by multiple reflections of the stress waves from the layer interfaces. 45,46 Simultaneous propagation of a wave of strong discontinuity in the proximal layer and a simple wave in the subsequent layers occurs when the layers' densities change in the direction of propagation of the primary wave.…”
Section: The Curves Of Performance Indicators For Honeycombs With Various N Under Dynamic Impactmentioning
confidence: 97%